The Metamorphosis of Places in André Malraux’s Les Noyers de l’Altenburgand Romain Gary’s Education européenne - Tame, Peter (Literatūra, 2022)
This article examines the importance of imaginary spaces and places (literary isotopias) in André Malraux’s Les Noyers de l’Altenburg (1943) and Romain Gary’s Education européenne (1945). It analyses the metamorphoses of space and place, together with the relationships between those spaces and the novels’ characters, in order to identify commonality as well as differences between the approaches of the two authors. The roles of nature, art and myth in the two novels are also considered, particularly in the context of war. Moreover, the article takes into account the humanism of both authors against the background of wartime. André Malraux’s crucial concept of metamorphosis finds significant echoes in Romain Gary’s novel Education européenne, particularly in the aspiration to transform the world, change mentalities and remake communities both in the national and international contexts. For both writers, the metaphysical struggle against death is often portrayed as being more important than the military conflict with the enemy. Moreover, the novels of both writers have undergone a number of literary metamorphoses in terms of textual genesis and generation. Although Romain Gary’s work is probably less well known today than that of André Malraux, we may find, in conclusion, that the former’s approach, style and content of thought are actually just as “modern” and appealing to readers nowadays.